Tinjauan Yuridis Terhadap Penguasaan Harta Warisan Oleh Salah Satu Ahli Waris Dalam Sengketa Waris: Studi Putusan Nomor 455/Pdt.G/2024/PN Jkt.Pst - Rayi Kharisma Rajib; Nurul Baitii F Wahid; Darian Ezra ‘Aabidah (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
The issue of inheritance disputes is one of the conflicts that frequently occur in society, particularly concerning the control of inherited property by one of the heirs without the consent of the other parties. This condition not only causes tension within family relationships but also raises complex legal issues. In civil law, inherited property is essentially the joint property of the heirs from the moment the deceased passes away as regulated in Article 833 paragraph (1) of the Civil Code, which states that the heirs automatically acquire rights to all the deceased's goods, rights, and receivables. In addition, the principle that no one can be forced to remain in an undivided state is affirmed in Article 1066 of the Civil Code, which provides a legal basis for fair division of inheritance. This study aims to examine the legal regulations regarding the control of inherited property by heirs according to civil law. and also analyzes juridically the withdrawal of the lawsuit in Decision Number 455/Pdt.G/2024/PN Jkt.Pst. The research method used is normative juridical with a statutory approach and a case approach, through the study of legal regulations, literature, and relevant court decisions.